Behaviour change: The impact of consumer trust on product purchase decision making - Johni Paul Karolus Pasaribu; Jones Parlindungan Nadapdap; Rismanto Gatot Trisilo; Andi Halim Rahman; Pupung Ismayanti (Universitas Sebelas Maret, 2024)
Business is an interesting thing among young people today, where business programs continue to be promoted and become the main thing so that economic stability continues like a rolling wheel. The purpose of this study was to determine the impact of consumer behaviour on product trust through social media on purchasing decisions with respondents being social media users. Social media, an expansive digital landscape fostering communication and interaction, emerges not merely as a conduit for social engagement but significantly as a hub for the strategic promotion and marketing of products, amplifying consumer interest and engagement. The method used in this research is a quantitative method with a direct survey and a questionnaire, the research sample is 120 community respondents who actively buy products through social media. The profound revelations gleaned from this study unveiled a pivotal correlation: the palpable influence wielded by-product trust cultivated through social media channels on the decisions to purchase. Notably, the findings underscore the compelling and direct positive impact wielded by-product trust engendered via social media interactions on shaping and actualizing consumer purchasing behaviors.